How EtnoEduction is Essential and Linked to the Science Learning in the 21st Century Paradigm? - I Made Citra Wibawa; I Wayan Widiana; Nyoman Jampel (Jurnal Edutech Undiksha, 2024)
Improving the quality of science education in elementary schools is not only crucial for fostering better understanding of science, but also for building a strong foundation for future scientific thinking and actions. This systematic review aims to explore and analyze various effective methods and strategies of science learning in elementary schools in the 21st century. This systematic review was designed based on relevant criteria from the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). The data were sourced from the utilization of electronic databases such as PubMed, ERIC, Scopus, and Google Scholar. The search keywords employed included “effective science learning”, “science in elementary schools”, and “21 century”. All papers were reviewed and quality assessment was performed. Fifteen studies were finally selected. Data were extracted, organized and analysed using a narrative synthesis. There are several factors influencing effective science education in the 21st century, including the incorporation of digital technology, cultural elements, contextual learning, adaptive approaches, and competency-based methods. Suitable strategies to support this science education include inquiry-based learning, project-based learning, cooperative learning, experiment-based learning, and game-based learning. Consequently, students greatly benefit from ethno-science education delivered through digital learning applications rooted in local cultural contexts.